2022
DOI: 10.1111/ajt.17093
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine services for living kidney donation: A US survey of multidisciplinary providers

Abstract: Individuals considering living kidney donation face geographic, financial, and logistical challenges. Telemedicine can facilitate healthcare access/care coordination. Yet difficulties exist in telemedicine implementation and sustainability. We sought to examine centers' practices and providers' attitudes toward telemedicine to improve services for donors. We surveyed multidisciplinary providers from 194 active adult US living donor kidney transplant centers; 293 providers from 128 unique centers responded to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 54 publications
0
6
0
1
Order By: Relevance
“…Second face-to-face visit with the nephrologist for full anamnesis and inform donor and recipient on risks and benefits of donation and transplantation adapted to their personal history. A design of the study plan from that moment, if intention to donate is confirmed [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…Second face-to-face visit with the nephrologist for full anamnesis and inform donor and recipient on risks and benefits of donation and transplantation adapted to their personal history. A design of the study plan from that moment, if intention to donate is confirmed [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…Asimismo, otro claro ejemplo de utilidad de la telemedicina en áreas de la medicina, tales como la nefrología, según Al Ammary et al (2022) se encontró heterogeneidad en la práctica actual de la telemedicina para la donación de riñón vivo en los Estados Unidos. Se halló que la telemedicina era principalmente utilizada por nefrólogos, cirujanos y psiquiatras/psicólogos para la evaluación y asesoramiento del donante, mientras que los trabajadores sociales utilizaban principalmente el teléfono y el video.…”
Section: Distribución De Años Con Referencias Revisadasunclassified
“…Heterogeneity in telemedicine practice across U.S. transplant centers exists. In a national survey of multidisciplinary providers at adult living donor kidney transplant centers [37 ▪▪ ], 70% of 128 represented centers plan to continue using telemedicine services for donor evaluation and/or follow-up care beyond the pandemic, whereas only 28% of centers used telemedicine prior to the pandemic. Utilization of telemedicine modalities varies by provider role.…”
Section: Telemedicine Practice Across Us Transplant Centersmentioning
confidence: 99%
“…Although many providers across specialties are willing to use telemedicine beyond the pandemic [37 ▪▪ ], they need education and training about best practices for using telemedicine and performing a limited physical examination virtually. Providers also need to be empowered with staff and technology support and private space to provide high standards of care [43,57,58].…”
Section: Factors Influencing the Implementation Of Telemedicine For L...mentioning
confidence: 99%